2021
DOI: 10.1111/nep.13830
|View full text |Cite|
|
Sign up to set email alerts
|

Filtering for the best policy: An economic evaluation of policy options for kidney replacement coverage in the Philippines

Abstract: Aim Kidney failure patients in the Philippines have free choice on their kidney replacement therapy (KRT), with a majority choosing haemodialysis (HD) over peritoneal dialysis (PD) and transplantation despite the inadequate coverage of HD. Although national health insurance coverage is limited, KRT remains to be one of the top benefits pay‐outs in the country. The study aims to identify the most cost‐effective policy strategy for financing KRT in the Philippines, in the context of a universal healthcare policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…Our baseline utility for dialysis patients in Thailand was relatively low (0.68 ± 0.1) (23). This was similar to what had been reported in a study from the Philippines (16). In contrast, a study from Malaysia showed a higher baseline utility (the utility was 0.91 for patients with ESKD) (24).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our baseline utility for dialysis patients in Thailand was relatively low (0.68 ± 0.1) (23). This was similar to what had been reported in a study from the Philippines (16). In contrast, a study from Malaysia showed a higher baseline utility (the utility was 0.91 for patients with ESKD) (24).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, a study from Malaysia showed a higher baseline utility (the utility was 0.91 for patients with ESKD) (24). The utility of patients after KT was even greater, ranging between 0.91 and 0.99 (16,24). These results reflect the improved quality of life after KT in real-world practice.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations